Determinants of Indonesian Coal Commodity Export Before and Post the Spread of the Covid-19 Policy - Risca Meyliawati; Denny Saputera; Gilang Nur Alam Alam; Dwi Fauziansyah Moenardi; Rizqi Muttaqin; Rina Ariyanthi Dewi (PT FORMOSA CENDEKIA GLOBAL, 2022)
As a fossil fuel, most of Indonesia's coal production to date is exported to various countries that still rely on this commodity as a source of electrical energy. With this pandemic, Indonesia's coal exports have decreased. Therefore, the need for coal to meet domestic demand will affect coal exports so that it will have an impact on economic growth. To determine the effect, this study was tested using qualitative research methods. The test results show that during the pandemic, coal consumption or demand decreases and has a negative impact on domestic economic growth.